Herramientas genómicas aplicadas al mejoramiento de soja convencional [Glycine max (L.) Merr.] - Bernardi, Clarisa Noelia; Fumero, María Verónica; Garis, Sol Belén; Lenzi, Lisandro German; Vanzetti, Leonardo Sebastian (Centro Regional Córdoba, INTA, 2023)
Poster